Predictive Value of Preoperative Diffusion Tensor Imaging for Evaluating Postoperative Outcomes of Supratentorial Glioma in the Motor Function Area - Duy Hung N; Duy Linh N; Ha Vi N; Van Anh NT; Dinh Hieu N; Dai Ha D; Minh Duc N (Dove Medical Press, 2023)
Nguyen Duy Hung,1,2,* Nguyen Duy Linh,3,4,* Nguyen Ha Vi,1 Nguyen Thi Van Anh,5 Nguyen Dinh Hieu,1,6 Duong Dai Ha,3,7 Nguyen Minh Duc8 1Department of Radiology, Hanoi Medical University, Hanoi, Vietnam; 2Department of Radiology, Viet Duc Hospital, Hanoi, Vietnam; 3Department of Surgery, Hanoi Medical University, Hanoi, Vietnam; 4Department of Surgery, Can Tho University of Medicine and Pharmacy, Can Tho, Vietnam; 5Department of Radiology, Hanoi Medical University Hospital, Hanoi, Vietnam; 6Department of Radiology, Ha Dong General Hospital, Ha Noi, Vietnam; 7Neurosurgery Center, Viet Duc Hospital, Hanoi, Vietnam; 8Department of Radiology, Pham Ngoc Thach University of Medicine, Ho Chi Minh City, Vietnam*These authors contributed equally to this workCorrespondence: Nguyen Minh Duc, Department of Radiology, Pham Ngoc Thach University of Medicine, 2 Duong Quang Trung Ward 12 District 10, Ho Chi Minh City, 700000, Vietnam, Email bsnguyenminhduc@pnt.edu.vnObjective: This study aimed to assess the predictive value of preoperative diffusion tensor imaging (DTI) data for surgical outcomes of patients with supratentorial glioma in the motor function area.Patients and Methods: This is a retrospective study of 43 patients receiving navigation-guided surgery for histopathologically demonstrated supratentorial glioma in the motor function area. All patients underwent preoperative 3 Tesla magnetic resonance imaging examinations with conventional and DTI sequences. Data on preoperative imaging and pre- and postoperative clinical characteristics of patients were retrospectively collected. Univariate and multivariate linear regressions were applied to analyze the relationships between preoperative parameters and pre- and postoperative muscle strength and the Karnofsky Performance Status (KPS) score.Results: Fourteen patients had low-grade gliomas and 29 had high-grade gliomas. Although the corticospinal tract (CST) score did not differ significantly between tumor grades, edema and deviation were common in low-grade gliomas (64.3%), while destroyed and infiltrated lesions were common in high-grade gliomas (58.6%). Muscle strength improved after surgery in the deviated tract group (40%) more than in the infiltrated tract group (33.3%). Two independent indices, preoperative muscle strength (p =  0.000) and glioma-to-CST distance (p =  0.001), were linearly related to postoperative muscle strength. The preoperative KPS score was the only indicator that affected the postoperative KPS score (p =  0.000).Conclusion: DTI should be considered in surgical management of supratentorial gliomas in the motor function area to determine the appropriate surgical strategy and predict the nature of the tumor and postoperative motor function.Keywords: diffusion tensor imaging, supratentorial glioma, preoperative planning, surgical outcomes, motor cortex